Experimental determination of restitution coefficient of garlic bulb based on high-speed photography - Yu, Zhaoyang; Hu, Zhichao; Peng, Baoliang; Gu, Fengwei; Yang, Ling; Yang, Mingjin (International Journal of Agricultural and Biological Engineering, 2021)
Restitution coefficient (RC) of garlic bulb is an important mechanical property that is required to establish the kinematics model of bulb collision and research the damage mechanism of bulb collision. In this study, kinetics equations of bulb collision were established based on Hertz's contact theory. The kinematics characteristics, elastoplastic deformation and contact damage during bulb collision were analyzed by using high-speed photography. The effects of bulb mass, moisture content, collision material, material thickness and release height on the RC were investigated by mixed orthogonal experiments and single- factor experiments. The results showed that the movement of bulb in the compression stage was translation, and the movement in the rebound stage was translation and rotation. During collision, the larger the rotational angular velocity of the bulb was, the smaller the measured RC would be. The contact damage of bulb included internal damage of the tissue, epidermis stretch and tear. The significance of effects of factors on RC decreased with the following sequence: collision material, release height, material thickness, bulb mass, and moisture content. Collision material, release height, material thickness, and bulb mass were significant factors. The RC between the bulb and Q235, nylon, and rubber decreased sequentially. The RC decreased with the increase of release height and bulb mass. The RC increased with the increase of material thickness of Q235, while it decreased with the increase of material thickness of rubber or Nylon. The determination coefficients of the regression equations between the significant factors and the RC were all greater than 0.96. The results will be helpful for damage mechanism analysis and design of garlic production equipment.Keywords: garlic bulb, collision, restitution coefficient, high-speed photography, experimental testsDOI: 10.25165/j.ijabe.20211402.5882Citation: Yu Z Y, Hu Z C, Peng B L, Gu F W, Yang L, Yang M J. Experimental determination of restitution coefficient of garlic bulb based on high-speed photography. Int J Agric & Biol Eng, 2021; 14(2): 81–90.